ISLAMIC CREED – RELEVANCE, SOURCES, AND CHRONOLOGY - Basheer Ahmed Dars; Sohaib Ahmed Indhar (دی اسکالر, 2018)
Scholars of Islam have given high importance to the matter of Aqeedah and the acquisition of correct belief in the light of the book of Allah and the sunnah of His noble messenger and our master, Muhammad ﷺ. Learning the correct Aqeedah is even considered more important than learning any other aspects of religion in line with opinions of the Sahabah and the salaf. It is important to note, however, that though the concepts and underpinning objective related to Aqeedah existed from the time of companions and Tabi’oon, this term per se did not exist at that time. In the subsequent generations, a number of books were written on the subject which were categorized under various titles such as as-sunnah, al-tauheed, al-itiqad and others. In this article, the reasons that led to the writing of these esteemed books are discussed. We have also compiled a comprehensive, though not all encompassing, list of classical works on Aqeedah which can be very useful for the future researchers exploring this subject as well as the students of sacred knowledge who can utilize it in referring to these classical works and gaining comparative understanding of how the great Imams from the salaf understood the matter of Aqeedah, what challenges they faced in their times and what was their approach to counter that.